The throne of fire - Riordan, Rick. (New York : Disney/Hyperion Books, 2011)
Carter and Sadie must outsmart the House of Life and the gods of chaos in order to complete their worldwide search for an ancient Egyptian book.
Keywords: Brothers and sisters -- Juvenile fiction; Gods -- Juvenile fiction; Secret societies -- Juvenile fiction; Family secrets -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Adventure stories; Egypt -- Juvenile fiction; Fantasy fiction